Texas Christmas defender - Goddard, Elizabeth (Love inspired suspense., 2017)
After earning the wrath of her brother, a notorious drug kingpin, Adriana Garcia has been in deep hiding on a remote Texas llama ranch. But when Texas Ranger Brent McCord manages to find her--leading her brother's men right to her, Adriana discovers she's a suspect in the murder of a border patrol agent.